Program Multi Level Marketing Generasi Berencana Kabupaten Pasuruan Perspektif Maslahah Mursalah - Fitria Dwi Murti; Zayin Chudlori (AL-HUKAMA, 2019)
This article discusses the theory of mashlahah mursalah on the Multi Level Marketing Planning Generation Program (MLM Genre) of the Family Planning and Women's Empowerment Office in Pasuruan Regency. From the research on the MLM Genre program organized by the Family Planning and Women's Empowerment Office of Pasuruan Regency, it can be concluded: First, this program has not been implemented properly because the program should have been implemented in every sub-district in Pasuruan Regency, which amounted to twenty-four Districts, but for now it is still running in five districts only. Among the factors is the lack of awareness of the Pasuruan community to participate in running the program. Second, the Multi Level Marketing Planning Generation Program organized by the Family Planning and Women's Empowerment Office of Pasuruan Regency in terms of activities and material delivered by the Family Planning and Women's Empowerment Office of Pasuruan Regency provides benefits for adolescents and the surrounding community who will get married. In the perspective of the maslahah mursalah, it has fulfilled the requirements of the mashlahah, and does not contradict to the texts, real, general in nature, and has many benefits.